2013
DOI: 10.1002/btpr.1791
|View full text |Cite
|
Sign up to set email alerts
|

Mycelium growth stimulation of the desert truffleTerfezia claveryichatin by β‐cyclodextrin

Abstract: The commercial value of Terfezia claveryi, an edible desert truffle with important gastronomic, nutritional, and antioxidant properties, has led to growing interest in its cultivation. The erratic and slow growth of T. claveryi mycelium in vitro represents an impairment to obtain mycorrhizal plants, and it makes necessary to find a new culture medium able to overcome these drawbacks. In this work, we analyze the effect of cyclodextrins (CDs) on the growth of T. claveryi mycelium. Different parameters, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Navarro-Rodenas et al [29] suggested that the ascocarp of T. claveryi may, at some development stages, become independent on nutrition from the host plant. In vitro, Lopez-Nicolas et al [30] confirmed the ability of the compound βcyclodextrin to stimulate the mycelial growth of T. claveryi. Slama et al [7] succeeded in the cultivation of Terfezia boudieri in the field, using the mycorrhizal plant of Helianthemum sessiliflorum in gypsy and sandy loam soils after one year.…”
Section: The Mycorrhizal Association Of Desert Trufflesmentioning
confidence: 95%
“…Navarro-Rodenas et al [29] suggested that the ascocarp of T. claveryi may, at some development stages, become independent on nutrition from the host plant. In vitro, Lopez-Nicolas et al [30] confirmed the ability of the compound βcyclodextrin to stimulate the mycelial growth of T. claveryi. Slama et al [7] succeeded in the cultivation of Terfezia boudieri in the field, using the mycorrhizal plant of Helianthemum sessiliflorum in gypsy and sandy loam soils after one year.…”
Section: The Mycorrhizal Association Of Desert Trufflesmentioning
confidence: 95%
“…3). This increase could be probably attributed to the fact that HP-b-CD acts as a carbohydrate source for fungi (Del Toro-Sanchez et al, 2010) or encapsulates substances produced by fungi that self-inhibit the mycelium growth (López-Nicolás, Pérez-Gilabert, García-Carmona, Lozano-Carrillo, & Morte, 2013). We should note that the chemical structure of CDs (hydrophilic nature and bulk volume) do not allow them, neither their inclusion complexes, to permeate biological membranes (Loftsson et al, 2005).…”
Section: Mycelium Growth Assaymentioning
confidence: 96%